School-Based Intervention to Improve Healthy Eating Practices Among Malaysian Adolescents: A Feasibility Study Protocol - Mohammadi, Shooka; Su, Tin Tin; Jalaludin, Muhammad Yazid; Dahlui, Maznah; Azmi Mohamed, Mohd Nahar; Papadaki, Angeliki; Jago, Russell; Toumpakari, Zoi; Majid, Hazreen A. (Frontiers in Public Health, 2020)
Introduction: School environments can influence students' dietary habits. Hence, implementing a healthy canteen intervention programme in schools is a recommended strategy to improve students' dietary intake. This study will evaluate the feasibility of providing healthier food and beverage options in selected secondary schools in Malaysia by working with canteen vendors. It also will assess the changes in food choices before and after the intervention. Methods: A feasibility cluster randomised controlled study will be conducted in six secondary schools (intervention, n = 4; control, n = 2) comprising of rural and urban schools located in Selangor and Perak states in Malaysia. Four weeks of intervention will be conducted among Malaysian adolescents aged 15 years old. Two interventions are proposed that will focus on providing healthier food options in the canteen and convenience shops in the selected schools. Interventions 1 and 2 will entail training the canteen and school convenience shop operators. Intervention 2 will be applied to subsidise the cost of low energy-dense kuih (traditional cake), vegetables, and fruits. The control group will continue to sell the usual food. Trained dietitians will audit the canteen menu and food items sold by the school canteen and convenience shops in all schools. Anthropometric measurements, blood pressure and dietary assessment will be collected at baseline and at the end of 4-week intervention. Focus group discussions with students and in-depth interviews with headmasters, teachers, and school canteen operators will be conducted post-intervention to explore intervention acceptability. Under this Healthy School Canteen programme, school canteens will be prohibited from selling “red flag” foods. This refers to foods which are energy-dense and not nutritious, such as confectionery and deep-fried foods. They will also be prohibited from selling soft drinks, which are sugar-rich. Instead, the canteens will be encouraged to sell “green flag” food and drinks, such as fruits and vegetables. Conclusion: It is anticipated that this feasibility study can provide a framework for the conception and implementation of nutritional interventions in a future definitive trial at the school canteens in Malaysia.